PENGARUH DEWAN PENGAWAS SYARIAH, PROFITABILITAS DAN LEVERAGE TERHADAP PENGUNGKAPAN ISLAMIC SOCIAL REPORTING (ISR) (Studi Pada Bank Umum Syariah di Indonesia Periode 2012-2016) - Siti Sara Rostiani; Tuntun A. Sukanta (Universitas Widyatama, 2018)
The purpose of this research is to find out the influence of sharia supervisory board, profitability, and leverage toward the disclosure of Islamic Social Reporting (ISR) at Sharia Commercial Bank in Indonesia during 2012-2016 and test it. Purposing sampling is the technique that been used in this research with the samples 9 Sharia Commercial Bank during 5 years observation respectively with the result obtained 45 samples. The analysis technique used in this research was multiple regressions. The analysis result shows that the sharia supervisory board has a positive significant influenced toward the disclosure of Islamic Social Reporting (ISR). While profitability and leverage have no significant influenced toward the disclosure of Islamic Social Reporting (ISR).